STRATEGI MANAJEMEN PENGUNJUNG UNTUK MENINGKATKAN JUMLAH KUNJUNGAN DI TELAGA WARNA PUNCAK BOGOR JAWA BARAT - Dela Safitri; Liliana Dewi (LPSDI Bina Patria, 2024)
This research aims to analyze the management strategy at Telaga Warna Puncak, Bogor West Java to increase the number of tourist visits. In this research, Telaga Warna is one of the natural destinations in Puncak, Bogor. This destination has great potential to be developed but there are still several problems in increasing the number of visitors. This research uses qualitative descriptive data analysis techniques and uses qualitative data analysis tools in the form of Nvivo 12 software.The results of this study use the concept of AIDA (Attention, Interest, Desire, Action), the strategy is focused on increasing promotion to attract potential tourists, attracting tourists' attention to visit the destination.This research is expected to provide information to destination managers to be more optimal in increasing the number of visits with visitor management strategies,